Surveillance and privacy – Beyond the panopticon. An exploration of 720-degree observation in level 3 and 4 vehicle automation. (August 2021) - Jannusch, Tim; David-Spickermann, Florian; Shannon, Darren; Ressel, Juliane; Völler, Michaele; Murphy, Finbarr; Furxhi, Irini; Cunneen, Martin; Mullins, Martin
Abstract: On the path to high-level vehicle automation, the degree of surveillance both inside and outside the car increases significantly. Consequently, ethical considerations are becoming central to questions around surveillance regimes and data privacy implicit in level 3 and 4 vehicle automation. In this paper, we focus on outputs from the EU Horizon 2020 project Vision Inspired Driver Assistance Systems (VI-DAS). In particular, we assess the VI-DAS 720-degree observation technology, critical to ensuring a safe Human Machine Interaction (HMI), from multiple theoretical perspectives to contribute to a better understanding of the phenomena of privacy. As a synonym for surveillance, we started our evaluation with Bentham's ideation of the panopticon. From there, it is a relatively short step to radical Foucauldian critiques that offered more dystopian technologies of power. However, both theorems demonstrate a limited understanding of the issue of data privacy in the context of safe transportation along the evolution of highly automated vehicles. Thus, to allow the debate to move beyond more binary discussions on privacy versus control/power and to a certain degree escape the shadow of the panopticon, we applied the Nissenbaum four theses framework of Contextual Integrity (CI). Her decision heuristic allowed us to introduce structure and a degree of precision in our thinking on the matter of privacy that represents a step forward to phenomena of privacy in a specific context. Our approach concludes that the VI-DAS 720-degree observation technology can respect the user's privacy through an appropriate flow of personal information. However, the flows of personal data must be strongly regulated to ensure that data is seen as a value in terms of a commodity to protect human life and not seen as an asset that needs to be turned into value in terms of capital or the facilitation of asymmetric power-relations. Highlights: The paper is based in part on outputs from the VI-DAS EU Horizon 2020 project. The question of privacy within future level 3 and 4 vehicles is discussed. Using Nissenbaum's framework of CI we escaped the shadow of the panopticon. A holistic determination of how in-vehicle observation can protect privacy while allowing the societal benefits is given.